Aspek hukum pidana cyberbullying di media sosial - Hatarto Pakpahan (Jurnal Cakrawala Hukum, 2020)
The current development of information technology has led to the increasinglyintense use of social media. However, the use of social media certainly raises bothpositive and negative sides. The use of social media in positive terms will greatlyhelp users to facilitate work activities and in terms of obtaining the desired informationor data. However, misuse of social media that causes harm to others, such as theact of “Bully” which causes the impact of the loss as a result of this action to othersis a form of cyber bullying. The method used in this paper is descriptive normativelegal research. In a related article, it presents an overview regarding the legal aspectsof cyber bullying and also the correlation between cyber bullying and socialmedia. Such acts of “bullying” conventionally and attacking the good name orhonor of others, including those expressed in public, can be punishable by the provisionsof the Criminal Code. The act of “Bully” which is carried out in cyberspace byusing the internet network (online) is charged with violating decency, insults, extortionor threats and also “Bully” in the form of electronic information on socialmedia that contains threats of violence or in the form of personal frightening arethreatened by article 29 in conjunction with Article 45B of Law of the Republic ofIndonesia No. 19 of 2016 amendments to the Law of the Republic of Indonesia No.11 of 2008 concerning ITE.How to cite item: Pakpahan, H. (2020). Aspek hukum pidana cyberbullying dimedia sosial. Jurnal Cakrawala Hukum, 11(3). 250-258. doi:10.26905/idjch.v11i3.5718.